Customers’ Driven Green Supply Management and Organization Performance - Shah, Asad Ullah; Siddiqui, Danish Ahmed (Global Disclosure of Economics and Business, 2019)
The purpose of this study is to identify the impact of various elements of customers’ driven green supply chain management such as internal green supply chain management, environmental collaboration with customers and environmental monitoring of suppliers over the environmental performance of an organization. For the purpose of this research, a survey was conducted in Karachi from the individuals involved in manufacturing and service providing industries. The survey was conducted using a questionnaire. The results indicated that all variables studied in this research including internal green supply chain management, environmental collaboration with customers’ and environmental monitoring of suppliers’ positively affect the overall environmental performance of a firm. An organization can enhance its environmental performance by effectively applying the strategies for green supply chain management. Green supply chain management has become a critical aspect in the current era as it has emerged as most vital attribute to sustainable environment.